Analisis Film Kartini Dalam Perspektif Kesetaraan Gender - Hamdja, Fansier; Qorib, Fathul; Dewi, Sulih Indra (Universitas Merdeka Madiun, 2020)
The purpose of this study was to determine the efforts of gender equality contained in the Kartini film through the semiotic study of Roland Barthes. Roland Barthes's analysis is used to find out the meaning of denotation, connotation, and myth in an image contained in artistic visualization, act, and dialogue in the film